The Relationship of Preventive Behaviors with the Incidence of Malaria in the Working Area of the Liukang Kalmas Health Center Pangkep District - Nurhayati, Nurhayati (Journal of Asian-african Focus in Health, 2023)
The aim of this research was to determine the relationship between preventive behavior and the incidence of malaria in the working area of the Liukang Kalmas Community Health Center Pangkep Regency . This research used analytical observational research , with a cross sectional design . Based on the results of research on the relationship between preventive behavior and the incidence of malaria in the work area of the Liukang Kalmas Health Center, Pangkep Regency , it was concluded that ; (1) Malaria prevention behavior among families at the Liukang Kalmas Community Health Center, Pangkep Regency, was mostly good, namely 113 people (83.1%) ; (2) The incidence of malaria in families at the Liukang Kalmas Community Health Center, Pangkep Regency, was mostly positive, namely 72 people (52.9%) ; (3) There is a relationship between prevention behavior and the incidence of malaria in the Liukang Kalmas Health Center Working Area, Pangkep Regency.